Translation and Its Role in the Plurality of the Gospel Text - Boudaoud, Mohamed El Mehdi (Journal of Ecohumanism, 2026)
The great multiplicity of Bible translations reflects a continuous effort to reconstruct a text presumed to be close to the earliest manuscript witnesses. However, this effort has not been isolated from the doctrinal, linguistic, and cultural backgrounds of the institutions and denominations that undertook the translation process. In many cases, translation went beyond its transmissive function to become an interpretive and exegetical practice through which theological perspectives and literary choices were projected onto the text. This led to the production of new formulations that, within the ecclesiastical context, came to be regarded as sacred texts in their own right rather than mere translations of a prior original. A review of the major ancient and modern translations reveals that manuscripts, despite their diversity and chronological and textual variation, represent the central challenge facing textual criticism in its attempt to recover the original biblical text amid historical gaps and the interweaving of textual layers. The factor of time further complicates this endeavor, especially with the discovery of manuscripts classified among apocryphal or pseudepigraphal literature, which raises growing theological and methodological concerns regarding the concept of the textual original and the limits of the possibility of its recovery.